Darboux curves on product time scales - Suroglu, Gulden Altay (Wiley, 2023)
In this study, we give the structure of ruled surfaces parameterized on a product time scale. Mean and Gaussian curvatures of these surfaces are constructed on distinct time scales. Then, we obtain principal curvatures for ruled surfaces. Finally, we will clarify the issue with some examples.
Keywords: Darboux curves; Darboux function; partial delta derivatives; product time scales; ruled surfaces